Mythology - Boswell, Helen ([Place of publication not identifed] : An Artemathene Book, 2012)
Hope Gentry doesn$1 (Bt believe in Fate. Born with an unusual power to see the dark memories of those around her, Hope just wants to be a normal teenager. But on the first day of her senior year of high school, she finds herself irresistibly drawn to a transfer student named Micah Condie. At first glance, Micah seems like a boy that most girls would dream about. But when Hope's powers allow her to discover Micah's darkest secret, she quickly becomes entangled in the lives of mythical entities she never dreamed existed. Was this her destiny all along? And will her powers help her survive the evil of the Demon Impiorum? Mythology isn$1 (Bt just for English class anymore.s
1. Fiery eyes -- 2. Surviving day one -- 3. Kidnapped -- 4. The mute button game -- 5. The tensest confrontation, ever -- 6. Bloody aura -- 7. In the city -- 8. Our first non-date -- 9. Confession time -- 10. Nature or nurture -- 11. My own worst memory -- 12. The scrimmage -- 13. What makes you the demon expert? -- 14. Troy's big party -- 15. Recovery -- 16. Not immortal -- 17. There are rules, and then there are rules -- 18. I am obligated to tell you -- 19. Run as fast as you can -- 20. Dinner date with my guardian and demon -- 21. More confessions -- 22. Deimos -- 23. Micah's family -- 24. Missing -- 25. Hope gentry, soul-seer -- 26. Ready or not, here I come -- 27. Father and son -- 28. The hunt -- 29. Emergency route -- 30. Gabriel -- 31. In the land of the dead -- 32. Elisha -- 33. We have immunity -- 34. Hunting Micah -- 35. Something dark -- 36. Enemy of the impiorum -- 37. Guardians.
Mythology /, Mythology
Keywords: AMERICAN FICTION